2016
DOI: 10.1007/s11136-016-1330-6
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measures change and quality of life in elderly people: a longitudinal population-based study in Southern Brazil

Abstract: Having excess weight and large WC in both waves was associated with lower QoL scores in elderly, but changing the anthropometric measures did not affect this outcome. Maintaining weight and WC within normal limits during aging can help to preserve QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
8
0
4
Order By: Relevance
“…One 2-year follow-up study conducted in England which included people ≥ 52 years old found that BMI had a protective effect on quality of life measured using CASP-19 (Control, Autonomy, Self-Realization and Pleasure) for women [31]. Another 4-year follow-up study in Brazil which investigated adults ≥ 60 years old found that maintaining a BMI within normal limits was helpful in preserving CASP-19 scores [32]. Still another 2-year follow-up study in Australia which included subjects 70–90 years old at baseline found that BMI had negative effects on independent living, social relationships and the experience of pain [33].…”
Section: Introductionmentioning
confidence: 99%
“…One 2-year follow-up study conducted in England which included people ≥ 52 years old found that BMI had a protective effect on quality of life measured using CASP-19 (Control, Autonomy, Self-Realization and Pleasure) for women [31]. Another 4-year follow-up study in Brazil which investigated adults ≥ 60 years old found that maintaining a BMI within normal limits was helpful in preserving CASP-19 scores [32]. Still another 2-year follow-up study in Australia which included subjects 70–90 years old at baseline found that BMI had negative effects on independent living, social relationships and the experience of pain [33].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for these findings is a greater severity and lower recovery of depressive symptoms among individuals with a higher level of obesity. Individuals with severe obesity have a higher frequency of chronic diseases, impairment of their quality of life, and reduced mental health, which may compromise the recovery from depressive symptoms (Luppino et al ., 2010; Meeks et al ., 2011; Volkert et al ., 2013; Tessari et al ., 2016). Furthermore, the stigma and discrimination faced by individuals with severe obesity (Jackson et al ., 2015) could aggravate this situation, generating greater psychological distress, low self-esteem, and body image dissatisfaction (de Souto Barreto et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The baseline study was conducted in 2009/10, and the first follow-up occurred in 2013/14. Details of this cohort have been published elsewhere (Tessari et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline study was carried out in 2009/10, and the first follow up in 2013/14. Details on sample calculation and sampling methods were previously published …”
Section: Methodsmentioning
confidence: 99%